“Vulneración de derechos fundamentales en la ejecución de la pena suspendida en procesos penales de omisión a la asistencia familiar” - Vasquez Martinez, Jenner Moises (2019)
ABSTRACT The main purpose of this research was to clarify certain concepts and dogmas in relation to fundamental rights that are violated in the execution of the suspended sentence in a process of omission to Family Assistance, which are the right to dignity, The best interest of the child and the right to food. The objective is to determine how, with a suspended sentence, this violation of fundamental rights occurs, taking into account that in both doctrine and jurisprudence there are more than two positions (aggravating) and mitigating (lacking financial resources) with The purpose of assessing whether a suspended sentence violates the fundamental rights mentioned above, analyzing doctrine, surveys and comparative law. In the present study we applied the type of qualitative research, the method used was the Historical - Causal, since it is that from the facts already produced that base the investigation and these same facts are those that produced effects. The cases of violation of fundamental rights taken for this study have been processed in the Superior Court of Justice of La Libertad, and the method of sampling was probabilistic and random. The research is exploratory in a first stage, then a type of descriptive research is made where the origins and effects of the problem are presented and finally an analytical investigation is finished when the hypothesis of the research work is contrasted with reality. This research work is important for society, so that it knows about the execution of the suspended sentence in the crime of omission of family assistance, violates fundamental rights as indicated above, which creates uncertainty in the population generating dissatisfaction in the Access to justice, so that the respective modification is proposed.